Retention Characteristics of CBTi144 Thin Films Explained by Means of X-Ray Photoemission Spectroscopy - G. Biasotto; A. Z. Simões; C. S. Riccardi; M. A. Zaghete; E. Longo; J. A. Varela (Advances in Materials Science and Engineering)
CaBi4Ti4O15 (CBTi144) thin films were grown on Pt/Ti/SiO2/Si substrates using a soft chemical solution and spin-coating method. Structure and morphology of the films were characterized by the X-ray Diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), Raman analysis, X-ray photoemission spectroscopy (XPS), and transmission electron microscopy (TEM). The films present a single phase of layered-structured perovskite with polar axis orient. The a/b-axis orientation of the ferroelectric film is considered to be associated with the preferred orientation of the Pt bottom electrode. XPS measurements were employed to understand the nature of defects on the retention behavior of CBTi144 films. We have observed that the main source of retention-free characteristic of the capacitors is the oxygen environment in the CBTi144 lattice.